2020
DOI: 10.1039/d0ra04018e
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature conversion of levulinic acid into γ-valerolactone using Zn to generate hydrogen from water and nickel catalysts supported on sepiolite

Abstract: Levulinic acid transformation into γ-valerolactone at 30 °C in water without molecular hydrogen addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In addition, the particle size was found to be of paramount importance in the reaction since Ni−Cu−OMA, the catalyst with the smallest particle size, provided the best performance. Previous studies have also reported that smaller particle sizes are favorable for LA conversion reactions [51–53] …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the particle size was found to be of paramount importance in the reaction since Ni−Cu−OMA, the catalyst with the smallest particle size, provided the best performance. Previous studies have also reported that smaller particle sizes are favorable for LA conversion reactions [51–53] …”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have also reported that smaller particle sizes are favorable for LA conversion reactions. [51][52][53] Furthermore, the synergistic effect of Ni and Cu was greatly affected by the fabrication strategy, which influenced the interfacial properties of Ni and Cu. The H 2 -TPR results indicated that a NiÀ Cu alloy might have been formed during the preparation of NiÀ CuÀ OMA, indicating that the Ni and Cu species were simultaneously reduced to generate the NiÀ Cu alloy of the Ni δ Cu 1-δ Al 2 O 4 (0 � δ � 1) form.…”
Section: Chemsuschemmentioning
confidence: 99%
“…However, it has an energetic density and cetane numbers lower than fossils fuels; therefore it has been studied more as an additive to fuels [17,18]. Moreover, it can be used as solvent to process the biomass, because it is able to dissolve biomass fractions avoiding the use of expensive solvents, enzymes or ionic liquids [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on the formation of GVL via levulinate ester or levulinic acid (LA) hydrogenation in one-pot employing heterogeneous catalysts have been reported. Non-noble metals such as Ni, Cu and Co have been widely studied because they are inexpensive and commercially available [14][15][16][17][18][19]. Huo et.…”
Section: Introductionmentioning
confidence: 99%